Attachment in Group Psychotherapy: Bridging Theories, Research, and Clinical Techniques. Issue 2 (3rd April 2017) - Marmarosh, Cheri L.
Abstract: Attachment theory is influencing the research and practice of group psychotherapy. The current issue highlights some of the bridges attachment theory has made both to contemporary group theories that include interpersonal theory and polyvagal theory and to approaches to group work that include mentalization-based group treatment. In addition, attachment theory is facilitating a richer understanding of group leadership, group cohesion, and the process of change that occurs during group interactions. The authors, who are researchers and group clinicians, reveal how attachment theory can be used to prepare members for group, to identify members who struggle to engage in conversations related to diversity, and to make sense of increasing disorganization that may occur as members become more intimate with one another during the group process. Group leaders will be able to apply these theories and techniques to their groups, and group researchers will be able to identify future studies that are needed to move the field forward.